Living donor liver transplantation in patients weighing ≥100 kg: Low graft weight and obesity do not impact outcomes. Issue 1 (January 2017) - Agarwal, Shaleen; Goyal, Neerav; Nayeem, Mohammed; Pareek, Shishir; Gupta, Subash
Abstract : Living donor liver transplantation (LDLT) in obese patients raises concerns with regards to obtaining grafts of "adequate" graft‐to‐recipient weight ratio (GRWR) and the impact of obesity on the outcomes of LDLT. LDLT outcomes in patients weighing ≥100 kg were compared with those weighing <100 kg. Patients weighing ≥100 kg were divided into 3 categories based on the GRWR of the grafts they received. Groups 1, 2, and 3 included patients with GRWR ≥0.8%, between 0.65% and 0.8%, and <0.65%, respectively. The 56 (6.5%) adult liver transplants were performed in patients weighing 100 kg or more. Except for higher mean body mass index (35.8 versus 25.2 kg/m 2 ; P value < 0.01) and grafts of lower GRWR in obese patients (0.74% versus 1.02%; P value < 0.01), all other parameters were similar between the 2 groups. Despite obesity and smaller grafts, the posttransplant outcomes such as day to normal bilirubin and international normalized ratio; infective, respiratory, and biliary complications; and hospital mortality were similar between the 2 groups. On comparing obese patients in the 3 GRWR categories, except for graft weight (985 versus 769 versus 646 g; P value < 0.01), all the pretransplant parameters were comparable. There was no significant difference in terms of graft function, postoperative morbidity, and hospital mortality between patients with grafts of normal GRWR and those with grafts of low and very low GRWR. Grafts of low GRWR give satisfactory results in obese patients undergoing LDLT and obesity does not adversely impact the outcome of LDLT. Liver Transplantation 23:35–42 2017 AASLD .